PENGARUH PROMOSI DAN KINERJA PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI PEMODERASI: STUDI PADA BANK BUMN DI DIY - Hadi Purnomo; Edi Santosa (Jurnal Riset Manajemen dan Bisnis, 2015)
Environmental dynamics shown by the uncertain situation faced by the company. Uncertain situationdue to a catastrophic event is one of the factors that need to be anticipated by the company. This studyaimed to analyze the effect of dynamic marketing capabilities to the performance of the creativeindustries and the dynamic moderating influence of the environment on their relationship in situationsof disaster that struck the Yogyakarta area.This study was conducted with 103 respondents.Respondents include business entrepreneurs of creative industries in Yogyakarta, especially in smalland medium business group. Hypothesis testing is done by regression analysis and regressionanalysis moderation. The results showed only two of the four hypotheses were supported, wherestrategic flexibility significantly affect firm performance, while dynamic environment do not moderatethe relationship between the two.Keywords: Dynamic Marketing Capability, Market Orientation, Strategic Flexibility,Environmental Dynamism, and Firm Performance